Ficções para o exílio: as formas políticas do cinema de Elia Suleiman - Maria Ines Dieuzeide Santos Souza (2018)
This research investigates the film trilogy composed by Chronicle of a Disappearance (1996), Divine Intervention (2002) and The Time that Remains (2009), directed by Elia Suleiman. In all three films, the director creates a character for himself who carries his given name and shares his biographical experience: a self-exiled Palestinian filmmaker attempting to return to his homeland. In pursuing the daily life and the violence of the Israeli occupation through a film form that values the frontal frames, the distance and fixity of the camera, the discontinuities and the staging that denatures the gestures, dialoguing with the burlesque style and making the cinematographic mediation explicit, these films seem to establish, through fiction, a visibility for the Palestinian situation that defies the logic imposed by the occupation. We seek to scrutinize the ways by which the fragmented spaces and the cutouts block the entry into the scene, and impose distances to the viewer; to understand the articulation proposed by these films between the centrality of the gaze in the frameworks and the episodic and decentered montage, which precludes a centralized narrative; to reflect on the elaboration of a form and a rhythm for daily life that interrupts the progressive passage of time. The analysis, immanent to the trilogy, examines how this film form establishes a formal dialogue with the particular condition of internal exile in which Palestinian people are separated from their own land, although living in the same place.